A wireless water pollution monitoring system - Muhammad Asyraf, Othman (2019)
Nowadays, water pollution is a serious threat not only to the environment and ecology but also effect the human as well. Before this, detecting and monitoring water only conduct manually by bringing sample from the river or sea to the lab. This project proposes a wireless water pollution monitoring system. Furthermore, this system are purposed to the staff of Jabatan Alam Sekitar to monitor the river more efficiently and reduces the workload during monitoring. This system integrated with sensors design to monitor the quality and pollution on the water. This system uses Arduino R3 to support and generate the sensors. The sensor use for this project is Ph sensor, Turbidity sensor and Flow sensor. The GSM devices acts as a connection between sensor and web application. This system also will pass all the information gather from the sensor to the web application via internet. The staff can monitor the river using the web application that will show the result of the water quality. Others, the system also provide an action taken to reduces the pollution base on the result of the water quality. Staff also can view data collected in form of graph by the system to use it to do analysis for future event. The methodology chosen for this project is Waterfall model which is well defined methodology and precise. In developing Wireless Water Pollution Monitoring system, Notepad++ and Arduino Software (IDE) are used to develop the interface and function that meet the requirement. In the end of this project, it is expected that the WWPMS meet the user requirement. Therefore, this application can give a convenient way to monitor the polluted river.